Swinging Sixties - British 1960´s Society in John Fowles' The Collector - Coufal, Martin (Univerzita Pardubice, 2019)
The thesis aims to analyse The Collector using the theory of encoding and decoding. To analyse the book properly, the thesis provides necessary historical, literary and cultural background of the 1960s. The practical part of the thesis analyses the dialogues of the book using the theory of encoding and decoding to find out why the characters of the book misunderstand the messages of each other and what these misunderstandings eventually lead to.
Britská společnost 60. let v díle Sběratel od Johna Fowlese
Keywords: Fowles, John; Sběratel; šedesátá léta; pracující třída; kódování a dekódování; postmodernismus; Fowles, John; The Collector; swinging sixties; working-class; encoding and decoding; postmodernism